The Definitive Guide to ImageMagick - Still, Michael (Apress : Imprint: Apress, 2006)
An open source project backed by years of continual development, ImageMagick supports over 90 image formats and can perform impressive operations such as creating images from scratch, changing colors, stretching, rotating, and overlaying images, and overlaying text on images. Whether you use ImageMagick to manage the family photos or to embark on a job involving millions of images, this book will provide you with the knowledge to manage your images with ease. The Definitive Guide to ImageMagick explains all of these capabilities and more in a practical, learn-by-example fashion. You'll get comfortable using ImageMagick for any image-processing task. Through the books coverage of the ImageMagick interfaces for C, Perl, PHP, and Ruby, you'll learn how to incorporate ImageMagick features into a variety of applications.